2015
DOI: 10.1002/adma.201500783
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Formation of Hollow Hybrids Composed of Cobalt Sulfides Embedded within Porous Carbon Polyhedra/Carbon Nanotubes for High‐Performance Lithium‐Ion Batteries

Abstract: 3D hollow hybrid composites with ultrafine cobalt sulfide nanoparticles uniformly embedded within the well-graphitized porous carbon polyhedra/carbon nanotubes framework are rationally fabricated using a green and one-step method involving the simultaneous pyrolysis and sulfidation of ZIF-67. Because of the synergistic coupling effects favored by the unique nanohybridization, these composites exhibit high specific capacity, excellent cycle stability, and superior rate capability when evaluated as electrodes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
316
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 630 publications
(326 citation statements)
references
References 35 publications
9
316
0
1
Order By: Relevance
“…1f). Although it is ideal to achieve phase pure cobalt sulfide materials via control over the sulfurization temperature, it is actually difficult to achieve this using the proposed experimental procedure, which is consistent with the recent reports, 45,46 where the authors used sulfur for the sulfurization of ZIF-67 under different temperatures and the formation of the assynthesized composites is complicated during the sulfurization and carbonization procedure. The XRD results clearly showed that with the increase of sulfurization temperatures, the XRD peaks for cobalt sulfide (mainly Co 1-x S phase) became more intense and sharper, accompanied with the appearing of Co 3 S 4 , indicating the growth of crystallites and crystallinity improvement of cobalt sulfide.…”
Section: Resultssupporting
confidence: 82%
“…1f). Although it is ideal to achieve phase pure cobalt sulfide materials via control over the sulfurization temperature, it is actually difficult to achieve this using the proposed experimental procedure, which is consistent with the recent reports, 45,46 where the authors used sulfur for the sulfurization of ZIF-67 under different temperatures and the formation of the assynthesized composites is complicated during the sulfurization and carbonization procedure. The XRD results clearly showed that with the increase of sulfurization temperatures, the XRD peaks for cobalt sulfide (mainly Co 1-x S phase) became more intense and sharper, accompanied with the appearing of Co 3 S 4 , indicating the growth of crystallites and crystallinity improvement of cobalt sulfide.…”
Section: Resultssupporting
confidence: 82%
“…According to the literature we reviewed, the mixed phase of cobalt sulfide is easily obtained during the preparation28, 29, 30, 31 and can be purified by subsequent annealing in air 32. Wu et al obtained a mixed phase of CoS and Co 9 S 8 by mixing ZIF‐67 with sulfur powder and annealing in an argon atmosphere 6. We find two reasons why carbon‐coated cobalt sulfide materials form a mixture phase through our experiments.…”
Section: Resultsmentioning
confidence: 65%
“…Recently, transition‐metal chalcogenides (TMCs) have attracted tremendous attention for its multitude of possible valence states, stoichiometric compositions, and crystal structure 4, 5, 6, 7. Compared with their oxide counterparts, TMCs usually exhibit better electrical conductivity, and thermal and mechanical stability 7.…”
Section: Introductionmentioning
confidence: 99%
“…For Ni-LVO, the increase in capacity during cycling was also commonly observed for metal oxides and may be attributed to the improved lithium diffusion kinetics by the gradual activation process and reversible reaction between materials and electrolytes. [36][37][38] For the LVO electrode, the discharge capacity decreased to 47% compared with the initial value. The coulombic efficiency of both LVO and Ni-LVO electrodes remained constant close to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…The extra capacity at low potential may be related to the decomposition of the electrolyte upon reduction with the formation of a gel-like polymeric film 31 and interfacial storage, 32,33 which has also been observed in other anode materials such as SnO 2 , 34 CoO 35 and CoS x . 36 The capacity of the LVO electrode decreased rapidly at 50 mA g − 1 . The Ni-LVO electrode exhibited higher capacity than the bare LVO electrode.…”
Section: Resultsmentioning
confidence: 99%